2019
DOI: 10.1002/ccd.28534
|View full text |Cite
|
Sign up to set email alerts
|

Venous access closure using a purse‐string suture without heparin antagonism or additional compression after MitraClip implantation

Abstract: ObjectivesThis observational study was designed to analyze the safety and feasibility of percutaneous skin closure using a purse‐string suture (PSS) after MitraClip procedures.MethodsForty‐one consecutive patients with severe mitral regurgitation who underwent MitraClip implantation from February 2018 to January 2019 at our institution received a PSS after percutaneous mitral valve repair before withdrawal of the 24‐French (Fr) sheath. Protamine was not administered after venous closure at procedure end. No co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…No difference was found regarding hematomas <5 cm (13.6% vs. 11.5%, P = 0.39) or >5 cm (8.7% vs. 7.8%; P = 0.69), arterio-venous fistulas (3.9% vs. 2.2%; P = 0.22), or pseudoaneurysm (0.87% vs. 7.8%; P = 0.69) [33]. Another study by Akkaya et al [23] reported that venous access site closure with a purse-string suture without the use of protamine or compression appears to be safe and feasible in patients undergoing mitral valve repair with MitraClip (Abbott Vascular, Santa Clara, CA, US) implantation using a 24 F caliber venous sheath. Similarly, Kypta et al [22] favored the safety of subcutaneous double purse-string sutures in patients on anticoagulation undergoing leadless pacemaker implantation using sheaths with 18-23 F internal diameter, and 27 F outer diameter.…”
Section: Purse-string Suturementioning
confidence: 93%
See 3 more Smart Citations
“…No difference was found regarding hematomas <5 cm (13.6% vs. 11.5%, P = 0.39) or >5 cm (8.7% vs. 7.8%; P = 0.69), arterio-venous fistulas (3.9% vs. 2.2%; P = 0.22), or pseudoaneurysm (0.87% vs. 7.8%; P = 0.69) [33]. Another study by Akkaya et al [23] reported that venous access site closure with a purse-string suture without the use of protamine or compression appears to be safe and feasible in patients undergoing mitral valve repair with MitraClip (Abbott Vascular, Santa Clara, CA, US) implantation using a 24 F caliber venous sheath. Similarly, Kypta et al [22] favored the safety of subcutaneous double purse-string sutures in patients on anticoagulation undergoing leadless pacemaker implantation using sheaths with 18-23 F internal diameter, and 27 F outer diameter.…”
Section: Purse-string Suturementioning
confidence: 93%
“…Multiple studies have established the efficacy and safety of the suture techniques, particularly FO8, even after procedures involving multiple femoral venous accesses with up to 24 F caliber sheaths. Suture techniques offer immediate hemostasis with comparable venous access complication rate to manual compression [5,8,16,22,23,25,32,33].…”
Section: Suture Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…Achieving hemostasis in venous access is similar to arterial district and can be achieved by different approaches (e.g., manual compression, mechanical external compression, and dedicated devices). However, only in the case of venous access, some studies reported purse-string suture as a valid alternative even in large bore [ 2 ]. Although very effective, the suture can be difficult to remove if the knot becomes buried in tissues narrowing the puncture sites, which may be puckered.…”
Section: Introductionmentioning
confidence: 99%